2019
DOI: 10.1002/ags3.12279
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of anticoagulant prophylaxis for prevention of postoperative venous thromboembolism in Japanese patients undergoing laparoscopic colorectal cancer surgery

Abstract: Aim To investigate the efficacy and safety of anticoagulant prophylaxis to prevent postoperative venous thromboembolism (VTE) during laparoscopic colorectal cancer (CRC) surgery, which is unknown in Japanese patients. Methods We conducted this randomized controlled trial at nine institutions in Japan from 2011 to 2015. It included 302 eligible patients aged 20 years or older who underwent elective laparoscopic surgery for CRC. Patients were randomly assigned to an intermittent pneumatic compression (IPC) thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
(39 reference statements)
1
11
2
Order By: Relevance
“…It is still controversial whether to administrate extended (4 weeks) or short-term (7-10 days until discharge) PTP in the postoperative period in patients undergoing major abdominal or pelvic cancer surgery ( Table 5 ). In fact, in Eastern populations which have less risk factors than Western counterparts, there are studies favoring for short-term prophylaxis or even observation without prophylaxis, without increasing incidence of VTE [ 25 - 27 ]. In a prospective double-arm study by Lee et al [ 12 ], 548 colorectal cancer patients had only mechanical prophylaxis such as anti-embolism stockings or elastic bandages without using PTP in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…It is still controversial whether to administrate extended (4 weeks) or short-term (7-10 days until discharge) PTP in the postoperative period in patients undergoing major abdominal or pelvic cancer surgery ( Table 5 ). In fact, in Eastern populations which have less risk factors than Western counterparts, there are studies favoring for short-term prophylaxis or even observation without prophylaxis, without increasing incidence of VTE [ 25 - 27 ]. In a prospective double-arm study by Lee et al [ 12 ], 548 colorectal cancer patients had only mechanical prophylaxis such as anti-embolism stockings or elastic bandages without using PTP in the perioperative period.…”
Section: Discussionmentioning
confidence: 99%
“…Routine screening with Doppler ultrasonography revealed that the DVT incidence after colorectal surgery was 3.0% [6]. Another study reported that DVT/PE incidence among laparoscopic colorectal surgery patients without anticoagulant prophylaxis was 5.1% using enhanced CT screening for all patients [7]. Higher incidence of DVT/ PE is reported in laparoscopic surgery for gastrointestinal cancer as 18.3% [9], and 24.3% in major abdominal surgery [10].…”
Section: Discussionmentioning
confidence: 99%
“…We compared the incidence of DVT/PE between acute appendicitis and other disease categories. Then, we compared the background data (operative time and age) between patients with acute appendicitis and those with colorectal cancer, as asymptomatic DVT/PE incidence among colorectal cancer patients had been well studied [6,7], and the number of operated cases are much higher in colorectal cancer than in other cancers. We thought DVT/PE incidence among colorectal cancer patients may provide a benchmark.…”
Section: Studiesmentioning
confidence: 99%
“…Five small Japanese randomised controlled trials assessed mechanical methods of thromboprophylaxis in surgical patients with cancer, with inconsistent findings. 44 , 45 , 46 , 47 , 48 In a network meta-analysis of patients with gynaecological cancer undergoing major abdominopelvic surgery, comparing different methods of thromboprophylaxis, intermittent pneumatic compression plus LMWH was best for VTE prevention. 42 …”
Section: Vte Prophylaxis In Patients With Cancermentioning
confidence: 99%